Exploring Writing Anxiety on Chinese EFL Undergraduate Thesis and its Coping Strategies - Peng Yanping (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Compared to other language skills, writing is a complicated skill that requires more efforts. Being English majors, they must master English language knowledge and express themselves correctly in English. Thesis writing has become one of the most challenging and difficult topics for Chinese students majoring in English as a foreign language (EFL). Affective factors have always been considered to be a major aspect affecting individuals’ writing. Among the emotional variables, anxiety cannot be ignored. Anxiety is one of the factors that affect the learning process. Second language writing anxiety has been investigated for several years but the researches on EFL undergraduate thesis writing anxiety at a Chinese context are quite a few. The study aims to examine the level, causes and coping strategies of writing anxiety among Chinese EFL undergraduate students. Both quantitative and qualitative methods were employed and the data was evaluated through SPSS. The findings of the study discovered that students experienced writing anxiety throughout the process. Writing anxiety is higher in the stage of pre-writing and post-writing than that in the stage of while-writing. Writing is negatively correlated with proficiency, with girls are more anxious than boys throughout the writing process. In addition to some possible causes of thesis writing anxiety, suggestions for students to alleviate writing anxiety were presented.